The moviment ofTaqui Onkoy (Huamanga in the 16th Century - Villegas P., Samuel Alcides (2011)
Taqui Ongoy or 7aki Un'fIlY was an índígenous movcmcnr which arase in 1560 in Huamsnga. Thc lireral rransladon from Quechua is "dancing sickness». The mcrnbcr of rhe movemcrus ralktng the huacas werc annoycd hy che expansión of Chrisrianiry, TIte huacas, Andean gods, began raking possession of me aborigines, making rhern dance and announce divino will ro restare [he pre-Hispaníc culture. Ir was bclíeved rhar thc huacas would rerurn wirh all thcir might and would defear rhe Spanish God, re-csrablíshing thc cquilibriurn ro a world wracked by rhe conquest. The lcader of che movcrnenr was Juan Chocnc and the visiror supprcssed Taqui Onkoy was Cristóbal de Albornoz,